2008
DOI: 10.1155/2008/458137
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Laparoscopic Liver Surgery: A Nine-Year Case Series

Abstract: Objective. This series describes a developing experience in laparoscopic liver surgery presenting results from 40 procedures including right hemihepatectomy, left lateral lobectomy, and microwave ablation therapy. Methods. Forty patients undergoing laparoscopic liver surgery between September 1997 and November 2006 were included. The data set includes: operative procedure and duration, intraoperative blood loss, conversion to open operation rates, length of hospital stay, complications, mortality, histology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Some authors have compared oncological results of laparoscopic and laparotomic surgery, including those of any kind of malignant lesion, and reported a similar margin width, recurrence risk, and overall survival rates [14, 23, 27, 45, 76, 77, 85]. Intraoperative laparoscopic ultrasonography has been associated with an increased rate of negative margins [19, 85].…”
Section: Oncological Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have compared oncological results of laparoscopic and laparotomic surgery, including those of any kind of malignant lesion, and reported a similar margin width, recurrence risk, and overall survival rates [14, 23, 27, 45, 76, 77, 85]. Intraoperative laparoscopic ultrasonography has been associated with an increased rate of negative margins [19, 85].…”
Section: Oncological Resultsmentioning
confidence: 99%
“…Little data are available on the LLR of colorectal liver metastases; only two papers have specifically focused on this topic [29, 46]. Further data are available from other laparoscopic series [10, 12, 23, 24, 30, 35, 40, 42, 43, 85], but such data are often incomplete and heterogeneous. Most relevant series are summarized in Table 5.…”
Section: Oncological Resultsmentioning
confidence: 99%
“…26 Coaptive coagulation uses a low temperature (50-100°C) to denature proteins in the tissues, forming a hemostatic protein coagulum that seals vessels and bile ducts. 34 Therefore, various surgical devices and techniques were used in the studies according to the historical background. Even though the superiority between these particular devices has not yet been proven, a surgical device bias could not be eliminated in the present meta-analysis.…”
Section: Bias Affecting the Results And Conclusionmentioning
confidence: 99%
“…Some studies comparing laparoscopic versus open procedures have demonstrated that the laparoscopic procedure may well be associated with less blood loss than open equivalents [16,17]. This observation may be due to the tamponading effect of a pneumoperitoneum [19]. Hence, blood loss could be minimized with this technique.…”
Section: Discussionmentioning
confidence: 99%